Visualization of size-dependent tumour retention of PEGylated nanographene oxide via SPECT imaging. Issue 39 (26th September 2016) - Cao, Tianye; You, Peihong; Zhou, Xiaobao; Luo, Jianmin; Xu, Xiaoping; Zhou, Zhiguo; Yang, Shiping; Zhang, Yingjian; Yang, Hong; Wang, Mingwei
Abstract : Sub-50 nm usNGO–PEG was confirmed to be the favorable size for faster and higher cellular uptake and efficient tumor accumulation than over-50 nm NGO–PEG. Abstract : PEGylated nanosized graphene oxides (NGO–PEG) and related derivatives have attracted extensive attention owing to their unique properties, which confer significant theranostic benefits for cancer treatment. The size of NGO–PEG varies largely, from tens of nanometers to micrometers, and the optimal size range with the most efficient tumor retention in vivo remains to be determined. For this purpose, we designed different sizes of NGO–PEG, specifically, ultra-small NGO–PEG (usNGO–PEG, sub-50 nm) and NGO–PEG (over 50 nm) and compared their biological behaviors in vitro and in vivo . Both NGO–PEGs exhibited nearly identical physicochemical properties and low cytotoxicity. Following Cy5.5 tagging, confocal microscopy fluorescence imaging revealed faster and higher dynamic cellular uptake of usNGO–PEG than NGO–PEG. Longitudinal, non-invasive visualization of the NGO–PEGs using single proton emission computed tomography (SPECT) imaging with 125 I-radiolabeling revealed that tumor retention of usNGO–PEG was significantly higher and longer compared to that of NGO–PEG, whereas the blood circulation and biodistribution of both NGO–PEGs were similar in major organs. In conclusion, Sub-50 nm was further confirmed to be the favorable size for efficient tumor accumulation of PEGylated GO via the enhanced permeability and retention (EPR) effect. We propose that the sub-50 nm NGO–PEG designed in this study may be effectively utilized to develop novel PEGylated GO-based nanoplatforms for multifunctional cancer nanotheranostics.